Investigation of modificated oculocardiac probe influence on functional state of cardio-vascular system and typological changes in cardiohemodynamic parameters in healthy young-aged female subjects - Palamarchuk, O. I.; Fushtey, I. M.; Chabanna, O. S.; Паламарчук, Олександр Іванович; Фуштей, Іван Михайлович; Чабанна, Олена Сергіївна (My University, 2024)
The goal of the study: to investigate typological changes in blood pressure parameters in the brachial artery during dosed compressive influence on the eyeballs in practically healthy young-aged female subjects and their possible diagnostic and prognostic significance.
Keywords: тези доповідей